Synthesis of 2-[{Bis-(2-chloroethyl)amino}methyl]-6,8-dinitro-1-(4-substituted phenyl)- 1H-quinazolin-4-one Derivatives as Possible Antineoplastic Agents - Murugan, V.; Kulkarni, Manijri; Anand, R.M.; Kumar, E.P.; Suresh, B.; Reddy, V.M. (Asian Journal of Chemistry, 2010)
Synthesis of six 2-{[bis-(2-chloroethyl)amino]methyl}-6,8-dinitro-1-(4-substituted)-1Hquinazoline-4-one derivatives is reported. The compounds contain nitro groups at positions 6 and 8 of quinazolinone moiety and a phenyl group at position 1. All the six compounds were incorporated with nitrogen mustard moiety. The synthesized compounds were screened for their anticancerous activity by short-term in vitro antitumor activity and in vivo anticancer activity by body weight analysis, mean survival time and percentage increase in life span methods in Swiss albino mice bearing DLA 1 x 106 cells/mL. Out of six compounds studied, compound IIIc (nitro-derivatives) showed significant anticancer activity.